2013
DOI: 10.1002/jbm.a.35067
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of mitochondrial signalling pathway in HGFs/S. mitiscoculture response to TEGDMA treatment

Abstract: Although triethylene glycol dimethacrylate (TEGDMA), a resin monomer widely used in dental practice, has been shown to have cytotoxic effects on eukaryotic cells, little is known about how the oral environment influences the cytotoxicity of this biomaterial. The aim of this study was to evaluate eukaryotic cell reaction to TEGDMA in terms of the production of reactive oxygen species (ROS), the expression of Bax, the disturbance of mitochondrial membrane potential (MMP), and the occurrence of apoptosis in an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…Gallorini et al . () reported a parallel trend for ROS‐COX‐2 levels leading to the hypothesis of a ROS‐mediated pathway involvement in COX‐2 activation .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Gallorini et al . () reported a parallel trend for ROS‐COX‐2 levels leading to the hypothesis of a ROS‐mediated pathway involvement in COX‐2 activation .…”
Section: Discussionmentioning
confidence: 93%
“…It has already been demonstrated that reactive oxygen species (ROS) play a role in COX-2 activation (Li et al 2013) in different experimental models. Gallorini et al (2013) reported a parallel trend for ROS-COX-2 levels leading to the hypothesis of a ROS-mediated pathway involvement in COX-2 activation.…”
Section: Discussionmentioning
confidence: 96%
“…Surprisingly, also, the nicotine-free fluids induced an increased ROS production after 24 h, indicating a role for the fluid itself in triggering the oxidative stress in HGFs. Basing on Bax recruitment and activation, involved in triggering the oxidative stress [31], we studied Bax expression, which is higher after 24 h both in nicotine-containing and in nicotine-free fluids. The nicotine seems to exert a time-dependent effect, while the nicotinefree fluid's toxicity may be milder because after 48 h, nicotine-free fluid-mediated Bax expression is similar to the control.…”
Section: Discussionmentioning
confidence: 99%
“…Human gingival fibroblasts (HGFs) were obtained at the Dental Clinic of the Department of Medical, Oral and Biotechnological Sciences of the University G. d’Annunzio. The tissue fragments were treated as previously described [ 25 ]. Signed informed consent was obtained from the donors.…”
Section: Methodsmentioning
confidence: 99%
“…Pooled unstimulated saliva was obtained from laboratory healthy staff (after no drinking or eating for two hours) by spitting method in polypropylene tube. The saliva was treated as previously described [ 25 ].…”
Section: Methodsmentioning
confidence: 99%